A prey-predator fractional order model with fear effect and group defense - Das, Meghadri; Samanta, G. P. (International journal of dynamics and control, 2021)
In this work, a fractional-order prey-predator system with fear effect of predator on prey population and group defense has been proposed. The existence and uniqueness of the system have been studied. Non-negativity and boundedness are also theoretically demonstrated. Analysis of local stability with examination of saddle-node and Hopf bifurcation at equilibrium points are performed by the help of numerical simulations along with analytical study. All the numerical simulations are performed using MATLAB and MAPLE.